Maximizing Student Learning with Semrush: A Project Based Learning Strategy for Crafting Effective Business Models - Renita Kawuryan; Umi Zunaidah; Sari Pratiwi (Jurnal Bisnis Digital, 2024)
This study examines the incorporation of Semrush into project-based learning to support university students in the creation of efficient business models. The project seeks to utilize Semrush for market research to improve students' critical thinking skills, boost their comprehension of business principles, and cultivate an entrepreneurial attitude. The study employs a qualitative research methodology with a case study design to compare a group of students utilizing Semrush with a control group. The results demonstrate that the integration of Semrush into project-based learning yields substantial advantages for students in the development of Business Model Canvas frameworks and the identification of business possibilities.